PENGARUH APE DARI BAHAN ALAM TERHADAP ASPEK PERKEMBANGAN ANAK USIA 4-6 TAHUN - Nurjanah, Elis; Masidah, Imas; Fifiet, Fifiet (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Teachers must have high creativity in developing visuals to support student learning in accordance with its provisions, namely learning while playing. Media such as safe, healthy and clean, make according to size, can to explore, can to experiment, can develop, encourage students to be creative, develop ability to use. Media from natural materials that can be developed by kindergarten students. Although natural materials are considered simple, but if there is high creativity by the teacher, the teacher will be able to produce a fun learning spirit. and can be involved. The existence of creative learning will stimulate achievement. from aspects of religious morality, physical motoric, language, cognitive, social emotional and art. Creativity at school will be the creativity that is done while playing. because the results for the material and the ease of being able to be in the surrounding environment.